Pneumococcal and influenza vaccination status of hospitalized adults with community acquired pneumonia and the effects of vaccination on clinical presentation - Ezgi Demirdogen Cetinoglu; Esra Uzaslan; Abdullah Sayıner; Aykut Cilli; Oguz Kılınc; Aysın Sakar Coskun; Armağan Hazar; Nurdan Kokturk; Ayten Filiz; Mehmet Polatli; on behalf of TURCAP Study Group (Human Vaccines & Immunotherapeutics, 2017)
Background: Previous reports have shown that vaccination rates of adult at-risk populations are low in Turkey. There are differing reports with regards to the effectiveness of the influenza and the pneumococcal polysaccharide vaccine (PPSV23) on the clinical outcomes of community acquired pneumonia (CAP). The purpose of this study was to analyze the influenza (FV) and pneumococcal vaccination (PV) status, the factors that influence the receipt of influenza/pneumococcal vaccine and the effects of prior vaccination on the clinical outcomes in adults hospitalized with CAP. Patients and Methods: Patients hospitalized with CAP between March 2009 and October 2013 and registered at the web-based Turkish Thoracic Society Pneumonia Database (TURCAP) were included in this multicentric, observational study. Of a total of 787 cases, data were analyzed for 466 patients for whom self-reported information on PV and FV was available. Results: In this adult population with CAP, the vaccination rate with both the pneumococcal and influenza vaccines was found to be 6%. Prior FV was found to be the sole variable that was associated with the receipt of PV [OR 17.8, 95% CI (25–75:8.56–37.01), p < 0.001]. Conversely, being vaccinated with PPSV23 was the only predictor of receipt of FV [OR 18.1, 95% CI (25 – 75:8.75 – 37.83), p < 0.001]. Compared to the unvaccinated cases, the chest radiograms of the vaccinated patients revealed less consolidation. The latter also reported fatigue, muscle pain and gastrointestinal symptoms less frequently. Although there was a trend for lower 30-day mortality and for lower rates of intensive care unit (ICU) admission, these did not reach statistical significance. A pneumonia severity index (PSI) score ≥ 90, CURB-65 score ≥3 and multilobar involvement, but not the vaccination status, were identified as independent determinants of ICU admission. Conclusions: This study showed that, among patients hospitalized with CAP, the FV and/or PV rates are low. Prior vaccination does not appear to significantly affect the clinical outcomes.